2021
DOI: 10.1093/jhps/hnab035
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of iliopsoas impingement after total hip arthroplasty: a minimum 2-year follow-up and comparison of tenotomy performed at the acetabular rim versus lesser trochanter

Abstract: Iliopsoas impingement is an underdiagnosed cause of groin pain after total hip arthroplasty (THA), being responsible for 4.4% of cases. Non-surgical treatment may be effective in ∼50% of cases. Endoscopic surgery has gained popularity as an option for non-responsive patients because of its non-invasive characteristics, faster recovery and encouraging results. This study compares two different sites of endoscopic psoas tenotomy performed following THA: at the edge of the acetabulum (AR) versus at the lesser tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…At a minimum follow-up of five years, the present study revealed a significant improvement in mHHS and OHS, exceeding the MCID in 92.5% of patients, as well as a satisfaction rate of 92.5%, and a rate of cup (with or without stem) revision of 14% (n = 8), although only two reoperations were directly linked to a failed tenotomy. These findings are in agreement to previous published studies on endoscopic tenotomy, that have reported satisfaction rates of 71-93%, mHHS between 75-89 points, and complication rates of 2-10% [2,3,17,26,41]. Studies on arthroscopic tenotomy have reported mean post-tenotomy HHS between 82-92 points and few to no complications and revisions [12,14,24,30,32,34,38,46].…”
Section: Discussionsupporting
confidence: 92%
“…At a minimum follow-up of five years, the present study revealed a significant improvement in mHHS and OHS, exceeding the MCID in 92.5% of patients, as well as a satisfaction rate of 92.5%, and a rate of cup (with or without stem) revision of 14% (n = 8), although only two reoperations were directly linked to a failed tenotomy. These findings are in agreement to previous published studies on endoscopic tenotomy, that have reported satisfaction rates of 71-93%, mHHS between 75-89 points, and complication rates of 2-10% [2,3,17,26,41]. Studies on arthroscopic tenotomy have reported mean post-tenotomy HHS between 82-92 points and few to no complications and revisions [12,14,24,30,32,34,38,46].…”
Section: Discussionsupporting
confidence: 92%